Managing arbuscular mycorrhizal fungi for bioprotection: Mn toxicity - Brito, I. (2013)
We investigated whether an intact extraradical mycelium (ERM) is more effective than other forms of propagule from indigenous arbuscular mycorrhizal fungi (AMF) in providing protection against stress to a host plant. The response of wheat (Triticum aestivum L.) to Mn toxicity was studied in a two-phase greenhouse experiment. In Phase 1, four Mn tolerant species from the natural vegetation, ranging from strongly mycotrophic to non- or weakly mycotrophic, were grown to develop different amounts of ERM. Wheat was then planted (Phase 2) with the ERM fragmented by sieving (Disturbed Treatment) or kept intact with no prior soil disturbance (Undisturbed Treatment). The growth of wheat was doubled by earlier and faster mycorrhizal colonization (AC) in the presence of an intact ERM at planting. There was a positive correlation between plant growth and the reduction of Mn and enhancement of P and S uptake into shoots. However, the growth of plants in undisturbed soil was significantly affected by the ERM developer species, which was not explained by differences in AC. Colonization starting from an intact ERM greatly enhanced the potential of AMF for protection against Mn toxicity. However, the degree of protection depended on the plant previously grown to develop the ERM, suggesting that there may be functional diversity within the ERM developed by mycotrophic plants of the natural vegetation.